1981
DOI: 10.1073/pnas.78.2.1229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chaotropic and antichaotropic agents on elution of poliovirus adsorbed on membrane filters.

Abstract: The association of poliovirus with membrane filters results from both electrostatic and hydrophobic interactions. At low pH, electrostatic interactions appear to dominate. However, at high pH, hydrophobic interactions appear to dominate with both Mfllipore and Zeta plus filters. With both filters, viral elution was prevented at high pH by the presence ofantichaotropic salts, which strengthen hydrophobic associations. This effect was antagonized by detergents and by chaotropic salts, which weaken hydrophobic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 17 publications
5
50
0
Order By: Relevance
“…From the results of this and other studies (6,12,20,21) we concluded that certain salt cations promote hydrophobic interactions between a virus and a filter or substrate. The cations that are most effective are smaller, monovalent or multivalent ions (6,12).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…From the results of this and other studies (6,12,20,21) we concluded that certain salt cations promote hydrophobic interactions between a virus and a filter or substrate. The cations that are most effective are smaller, monovalent or multivalent ions (6,12).…”
Section: Discussionmentioning
confidence: 85%
“…In fact, chelators have been found to promote, rather than interfere with, virus adsorption to microporous filters (6). The study of Farrah (6) and other studies showed that increased virus adsorption to certain microporous filters in the presence of cations and anions was influenced by hydrophobic interactions (6,12,21). Therefore, the adsorption of MS2 and poliovirus 1 in the presence of salts to filters was best explained by the presence of hydrophobic interactions between the filters and the viruses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This characteristic of urea was thought to contribute to the efficient extraction of crude protein and isolation of VBPs from bacterial cultures derived from activated sludge. The mechanism of adsorbing VBPs to the viral peptide in the affinity column cannot be explained by the simple electrostatic attraction and hydrophobic effect, although they have been reported as main factors in the adsorption of viruses to several substances, such as clay, sandy soil, estuarine sediments, and so on (5,6,21,22,26,39). Under the condition of the start buffer (pH 8.0), the net charge of the viral peptide in the affinity column was expected to be negative, because the pI of the immobilized viral peptide was estimated to be 3.88 (34).…”
Section: Vol 70 2004 Virus-binding Proteins Recovered From Sludge Cmentioning
confidence: 99%